2010
DOI: 10.1002/jcc.21675
|View full text |Cite
|
Sign up to set email alerts
|

A reoptimized GROMOS force field for hexopyranose‐based carbohydrates accounting for the relative free energies of ring conformers, anomers, epimers, hydroxymethyl rotamers, and glycosidic linkage conformers

Abstract: This article presents a reoptimization of the GROMOS 53A6 force field for hexopyranose-based carbohydrates (nearly equivalent to 45A4 for pure carbohydrate systems) into a new version 56A(CARBO) (nearly equivalent to 53A6 for non-carbohydrate systems). This reoptimization was found necessary to repair a number of shortcomings of the 53A6 (45A4) parameter set and to extend the scope of the force field to properties that had not been included previously into the parameterization procedure. The new 56A(CARBO) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
264
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(281 citation statements)
references
References 352 publications
(729 reference statements)
8
264
0
1
Order By: Relevance
“…However, there is some evidence to suggest that the simulations presented here are sampling the correct exocyclic conformation for these solvent-exposed groups. Recent experimental data suggests that GT may be more populated than GG for Glc in solution (Hansen and Hünenberger, 2011). X-ray data for cellobiose has shown that the two exocyclic groups in the crystal structure adopt the GT conformation (Chu and Jeffrey, 1968).…”
Section: Comparison With Previous Experimental and In Silico Datamentioning
confidence: 99%
“…However, there is some evidence to suggest that the simulations presented here are sampling the correct exocyclic conformation for these solvent-exposed groups. Recent experimental data suggests that GT may be more populated than GG for Glc in solution (Hansen and Hünenberger, 2011). X-ray data for cellobiose has shown that the two exocyclic groups in the crystal structure adopt the GT conformation (Chu and Jeffrey, 1968).…”
Section: Comparison With Previous Experimental and In Silico Datamentioning
confidence: 99%
“…Aqueous cellotetraose was modeled using both the GROMOS 56 carbohydrate force field (Hansen and Hünenberger 2010) in combination with the SPC/E model (Berendsen et al 1987) for water, and the CHARMM C35 parameter set (Guvench et al 2008;Guvench et al 2009) together with TIP3P water (Jorgensen et al 1983). Water molecules were kept completely rigid using SETTLE (Miyamoto and Kollman 1992), and all covalent bonds in cellotetraose were kept at their equilibrium distances using P-LINCS (Hess 2008).…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…8,9 Molecular dynamics (MD) simulations have proven to be a useful tool for providing a link between dynamics and structure. Many force fields have been extensively parameterized for carbohydrates, [10][11][12][13][14][15][16][17] and have been used to provide details of the structure and dynamics at an all atom (AA) level; for example to explore the ring puckering of glucose, 18,19 conformational changes in disaccharides and trisaccharides. 11,[20][21][22] However, previous MD studies of amylose have mainly dealt with small amylose fragments in water or studies of V-amylose in low polarity solvents.…”
Section: Introductionmentioning
confidence: 99%
“…46 to keep using them for the remainder of this work. Note that an improved GROMOS-based carbohydrate force field 19 has recently been released that might remedy some of the issues observed here.…”
mentioning
confidence: 97%